2021
DOI: 10.1007/s00417-020-05054-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reading with a mobile phone and text on accommodation in young adults

Abstract: Purpose To investigate the effects of reading with mobile phone versus text on accommodation accuracy and near work-induced transient myopia (NITM) and its subsequent decay during near reading in young adults with mild to moderate myopia. Methods The refractions of 31 young adults were measured with an open-field autorefractor (WAM-5500, Grand Seiko) for two reading tasks with a mobile phone and text at 33 cm. The mean age of the young adults was 24.35 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
2
9
3
Order By: Relevance
“…The findings of Hue et al 19 (target at 33 cm) and Park et al 15 (target at 40 cm) indicated that watching a video on a digital screen (iPod, smartphone) caused a greater lag of accommodation when compared to reading text on paper. Furthermore, the results from the current study showed a significant difference in the lag of accommodation between reading text on paper and on a smartphone (the lag being greater with the smartphone), while more recent findings by Liang et al 27 found no significant difference in the lag of accommodation (at 33 cm) when reading text on a smartphone or paper. However, in the study of Liang et al, 27 different targets were used for the visual tasks and the measurement of accommodation.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The findings of Hue et al 19 (target at 33 cm) and Park et al 15 (target at 40 cm) indicated that watching a video on a digital screen (iPod, smartphone) caused a greater lag of accommodation when compared to reading text on paper. Furthermore, the results from the current study showed a significant difference in the lag of accommodation between reading text on paper and on a smartphone (the lag being greater with the smartphone), while more recent findings by Liang et al 27 found no significant difference in the lag of accommodation (at 33 cm) when reading text on a smartphone or paper. However, in the study of Liang et al, 27 different targets were used for the visual tasks and the measurement of accommodation.…”
Section: Discussioncontrasting
confidence: 84%
“…Furthermore, the results from the current study showed a significant difference in the lag of accommodation between reading text on paper and on a smartphone (the lag being greater with the smartphone), while more recent findings by Liang et al 27 found no significant difference in the lag of accommodation (at 33 cm) when reading text on a smartphone or paper. However, in the study of Liang et al, 27 different targets were used for the visual tasks and the measurement of accommodation. In the present investigation, we used the same targets for both the visual tasks and the accommodative response measurement.…”
Section: Discussioncontrasting
confidence: 84%
“…Another study by Kim et al [32] showed an increase in the lag of accommodation after using a smartphone dependent on the vergence function of the subject's eyes. Liang et al [23] assessed the lag of accommodation after a 40-minute use of a smartphone and reading a printed paper and showed no increase in the lag of accommodation after near work, which is consistent with the results of a study by Kang et al [12]. In their study, lag of accommodation was assessed after near activity with smartphone and tablet, and after using these devices no significant difference in the lag of accommodation was seen.…”
Section: Discussionsupporting
confidence: 76%
“…The test results did not show statically significant differences between different activities; however, the number of participants in that study was small. Another study showed no significant difference in the mean of lag of accommodation after two near work, reading a book, and using a smartphone, [23]. In this study, the lag of accommodation, after 40 minutes of near work at a distance of 33 cm with a smartphone and reading book was examined.…”
Section: Introductionmentioning
confidence: 79%
“…Currently, computers, communication, and consumer electronics are popular, and the age of users is decreasing year by year. These electronic reading devices make viewing distances closer, which causes eye fatigue [20][21][22][23]. In order to reduce accommodation and slow the progress of myopia, this study proposes a new simple design of a double-mirror system (DMS) to extend viewing distance; while an object is still placed at a near distance, a virtual image is located further in front of the eye, resulting in accommodative relaxation.…”
Section: Introductionmentioning
confidence: 99%